EFFECTIVENESS OF TEACHING USING MULTIMEDIA COMPUTER GRAPHICS IN TEACHING "VIEWS, CUTS, SECTIONS" - Qozaqova Munojat Sharifjanovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
. The article provides recommendations on teaching the subject of views, cuts, sections in engineering and computer graphics with the help of modern computer programs.